Six-membered, chiral NHCs derived from camphor: structure-reactivity relationship in asymmetric oxindole synthesis - Spallek, Markus Jürgen; Riedel, Dominic; Rominger, Frank; Hashmi, A. Stephen K.; Trapp, Oliver (Organometallics, 2012)
A series of three chiral, expanded six-membered NHC-palladium(II) complexes was prepared with successively increased sterical demand, while retaining natural d-(+)-camphor as a chiral motif. The catalysts showed different reaction profiles in the asymmetric, intramolecular α-arylation of amides. The molecular structure of two N-heterocyclic and one nitrogen acyclic carbene palladium isonitrile complex was unequivocally determined by X-ray crystallographic analysis. The results reported herein account for a correlation of catalytic activity and enantiodiscrimination in relation to the degree of chiral substitution and steric congestion at the metal center. The modular and convergent synthetic route of these air- and moisture-stable palladium isonitrile complexes underlines the usefulness of this approach.